NUMERICAL ANALYSES TO OBSERVE THE PERFORMANCE OF A MONUMENTAL BUILDING AT THE UNIVERSITY OF BENGKULU, INDONESIA - Lindung Zalbuin Mase; Salsabhila Isdianty; Khairul Amri (Rudarsko-geološko-naftni Zbornik)
The Integrated Laboratory Building of Political and Social Science Faculty, located in a seismic-prone area, has been the subject of a comprehensive study of its performance using seismic response analysis. This research has yielded significant findings, gathering crucial secondary data, such as soil layers, bedrock depth, building structure, and earthquake wave information. The seismic response analysis, conducted by referencing the synthetic earthquake wave from the Bengkulu–Mentawai earthquake in 2007, with a magnitude of Mw 8.6, has provided a comprehensive overview of the earthquake waves at the foundation soil layers. The data, analysed using the finite element method to understand the structural response, revealed that the Peak Ground Acceleration (PGA) and amplification factor at the surface soil layer are 0.220g and 1.429, respectively. The most critical PGA and amplification factors at the foundation soil layer are 0.147g and 0.955. Structural analysis has revealed internal forces and beam elements experiencing over-strength, necessitating retrofitting the affected structural elements to reduce the impact. One practical and highly effective method of retrofitting involves increasing the beam dimensions by 53.12%. With retrofitting, the impact of structural deformation can be minimised, enhancing the building’s resilience in case of an earthquake of equal or greater magnitude. These findings underscore the importance of our research and highlight the significant role of engineers, architects, and researchers in ensuring the safety and longevity of structures in seismic-prone areas.